(untitled) (World Economics and Finance Bulletin, 2024)
This paper addresses the role of integration between shared value creation and sustainable manufacturing in achieving cost reduction and improving corporate performance by analyzing how shared value creation interacts with sustainable manufacturing methods. To this end, the paper proposes that integration between a shared value creation strategy and sustainable manufacturing positively contributes to reducing costs for economic units by improving the efficient use of available resources, reducing loss, and improving technical innovations. Therefore, these actions enhance economic unit’s competitiveness and achieve sustainable economic, social, and environmental benefits. Also, the paper recommends the formulation of comprehensive strategies that help create shared value with society, invest in sustainable manufacturing, and apply effective cost-cutting methods. The study was applied to Zawraa General Electrical Industries Co., with the relevant data collected and descriptively analyzed from 2015 to 2021. Furthermore, this paper contributes to the relevant literature on how to balance environmental and economic objectives. Finally, the paper aims to provide a practical framework for companies seeking to improve their financial performance through their commitment to social responsibility and sustainability